Application of nuclear medicine to achieve less invasive surgery for malignant solid tumors in children. Issue 6 (10th November 2014) - Hotta, Ryo; Fujimura, Takumi; Shimojima, Naoki; Nakahara, Tadaki; Fuchimoto, Yasushi; Hoshino, Ken; Morikawa, Yasuhide; Matsufuji, Hiroshi; Kuroda, Tatsuo
Abstract: Background: The use of nuclear medicine for the management of malignant tumor, such as radioguided surgery and sentinel lymph node biopsy (SLNB), has been widely accepted in the adult practice. However, there are very few studies to apply those techniques for pediatric diseases. The aim of this study was to investigate the feasibility of application of nuclear medicine in surgery for neuroblastoma (NB) or rhabdomyosarcoma (RMS) in children. Methods: Radioguided surgery using 123 I‐metaiodobenzylguanidine was performed on six children with NB. SLNB using technetium‐labeled tin or sulfur colloid was performed on two children with perineal RMS. Histological evaluation of resected specimens was performed to determine the accuracy of intraoperative detection and SLNB. All patients were evaluated for overall survival and complications. Results: Intraoperative tumor localization using hand‐held gamma probe was helpful in 85.7% of NB patients. Sensitivity and specificity of this technique were 81.8% and 93.3%, respectively. There were no postoperative complications, and four out of five patients with high‐risk NB experienced disease‐free survival (median follow up, 57 months). Sentinel lymph nodes were easily detected in patients with perineal RMS, and histological assessment revealed complete consistency with regional lymph node status. Conclusions: Nuclear medicine may have a potential application in the use of less invasive surgery for advanced NB or perineal RMS, the two most challenging pediatric malignancies.